3D TiO2 nanotube arrays with anatase-rutile phase junction and oxygen vacancies for promoted photoelectrochemical water splitting. (2nd February 2023) - Meng, Ming; Li, Chunyang; Li, Jitao; Wu, Juan; Feng, Yamin; Sun, Lingling; Yuan, Honglei; Liu, Kuili
Abstract: Constructing TiO2 phase junction with visible light response, effective separation and transfer of photogenerated charges is desperately needed for photoelectrochemical water splitting. Herein, 3D-TiO2 nanotubes arrays-based phase junction consisted of anatase core and rutile shell as well as oxygen vacancies are successfully fabricated via a new one-step annealing method in Ar atmosphere. The synergistic effect of phase junction and oxygen vacancies not only boosts the separation of photogenerated charges, but also enhances the utilization efficiency of the incident, reflected and/or refracted visible light captured by the 3D configuration. Moreover, the oxygen vacancies can act as electron donors, which could effectively improve the electrical conductivity, and hence further accelerate the separation and transfer of photogenerated charges. Benefiting from these advantages, the optimized 3D-TiO2 NTAs-based phase junction display a maximal photocurrent density of 1.5 mA cm −2 at 0.22 V vs. Ag/AgCl with Faradic efficiency of 100%, which is approximately 1.9 folds higher than that of pure anatase 3D-TiO2 NTAs. The technique and strategy could also be extended to other application of TiO2 NTAs such as solar cells and photocatalysis.